Real-world data-based assessment of therapy-related myeloid neoplasms after poly(ADP-ribose) polymerase inhibitor treatment in ovarian cancer - Uekusa, Ryosuke; Yokoi, Akira; Watanabe, Eri; Inoue, Mikako; Mizuno, Katsuhiko; Yoshida, Kosuke; Yoshikawa, Nobuhisa; Niimi, Kaoru; Suzuki, Shiro; Kajiyama, Hiroaki (Frontiers in Oncology, 2026)
BackgroundPoly(ADP-ribose) polymerase inhibitors (PARPi) have significantly improved outcomes in ovarian cancer. However, therapy-related myeloid neoplasms (t-MNs) have emerged as rare but serious late complications. Although an increased incidence of t-MNs has been reported following PARPi exposure, clinical predictors remain poorly understood.MethodsThis retrospective study analyzed 181 patients with ovarian cancer treated with PARPi at two Japanese institutions. Clinical characteristics and routine hematologic parameters were compared between patients with and without t-MNs. Hematological values were assessed at initial diagnosis, PARPi initiation, 4 weeks after initiation, and at nadir within 12 weeks. Relative changes from initial diagnosis and from PARPi initiation to nadir were also evaluated.Resultst-MNs developed in 6 (3.3%) patients. All patients in the t-MN group had received multiple platinum-containing regimens, and in five of the six cases, t-MN was diagnosed more than 5 years after initial diagnosis. No definitive clinical predictors were identified, although the t-MN group tended to have higher body mass index. Median white blood cell (WBC), hemoglobin, and platelet counts, as well as their relative changes from initial diagnosis or PARPi initiation to nadir, did not differ significantly between the groups. However, the t-MN group exhibited a larger reduction in WBC count from PARPi initiation to nadir, not statistically significant.ConclusionsThis real-world study highlights the importance of survivorship care in the era of improved outcomes for ovarian cancer. Continued long-term hematologic monitoring, along with the collection of more cases, is essential to elucidate risk factors for t-MNs in patients receiving PARPi therapy.